The Case Words Muz and Strom in the New Grammar Akademicka gramatika spisovne cestiny - Bednarikova, Bozena (Bohemica Olomucensia, 2016)
The beginning of the 21st century (especially its second decade) brought several attempts at comprehensive grammar of Czech. The long-awaited event, however, was processing the new academic Czech grammar. In 2013 the grammar Akademicka gramatika spisovne cestiny (Sticha et al. 2013). The grammar, although it bears the name of "academic" is far from being an academic grammar in the above sense. On the contrary, the extensive grammar should be according to the words of the editor a practical handbook for broad public, which should provide an ordered array of information about the natural rules of Czech grammar. Almost half of the range of academic grammar is covered by the chapter The Grammar of the Word, which can be a sign of how much weight is attached to it by the authors. About 200 pages (out of 450) are devoted to word-formation. One of the key issues of currrent functionally oriented grammatical descriptions are the competence and scope of morphology. The specific sub-issue is finding the boundaries between inflection and derivation (word formation). The new academic grammar seems to be promising that this limit be successfully overcome. This expectation was not fulfilled though. The paper attempts to analyze the shortcomings of the underlying theories and faulty handling of terminology, questionable interpretations and incompatibility of the individual parts which, unfortunately, significantly reduce the value of the new academic grammar. The lack of conceptual and methodological background are demonstrated in (mis)interpretation of the illustrative case words muz and strom.
Keywords: academic grammar; word; morphology; wordformation; derivation; infection; zero morpheme